1999
DOI: 10.1023/a:1020496330424
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although the fertilization rate of oocytes and the pregnancy rate were not significantly different between smokers and nonsmokers, we found significantly alterated hormonal parameters and negatively influenced oocyte parameters, particularly after clomiphene stimulation. So we might consider using only GnRHa protocols for smoking patients. Additionally, we advise our patients to stop smoking before an IVF-ET treatment because of the complex effects of smoking on the reproductive and hormonal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Tobacco consumption can result in an alteration of ovarian reserve, negative influence on the uterine receptiveness ( Soares et al , 2007 ) and possibly on the fertilization and embryo development ( Hassa et al , 2007 ; Jennings et al , 2011 ; Huang et al , 2009 ). Concerning IVF cycles, at present, the majority of the studies available report that smokers experience lower ovarian response to COH ( Neal et al , 2005 ; Weigert et al , 1999 ), and finally lower implantation rate ( Dessolle et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco consumption can result in an alteration of ovarian reserve, negative influence on the uterine receptiveness ( Soares et al , 2007 ) and possibly on the fertilization and embryo development ( Hassa et al , 2007 ; Jennings et al , 2011 ; Huang et al , 2009 ). Concerning IVF cycles, at present, the majority of the studies available report that smokers experience lower ovarian response to COH ( Neal et al , 2005 ; Weigert et al , 1999 ), and finally lower implantation rate ( Dessolle et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Not all epidemiological studies have found negative associations between smoking and ART success [ 13 , 28 ]. Although differences in study design and power may have influenced these results, these studies also tended to analyze clinical outcomes only among cycles reaching the point of embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that 10 of 33 smoker women (30%) and 47 of 133 nonsmoker women achieved a positive pregnancy (35.3%) (P > 0.05) (28). However, some studies reported that smoking has no effect on pregnancy rates (4,6,14,15,34,(36)(37)(38). In our study, we determined that the difference in FF cotinine concentrations between women with positive pregnancy test results and women with negative pregnancy test results was statistically insignificant ( Table 2, P > 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…It has been also shown that being exposed to secondhand smoke has similar negative effects on the reproductive health and outcomes of ARTs (10)(11)(12)(13). In contrast, there have been some studies showing that there is no measurable effect of recent or ongoing smoking on ARTs outcomes (4,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%